ChemInform Abstract: The Ligand Influence in Stereoselective Carbene Transfer Reactions Promoted by Chiral Metal Porphyrin Catalysts. Issue 50 (November 2016) - Intrieri, Daniela; Carminati, Daniela Maria; Gallo, Emma
Abstract: Review: 83 refs.